EDUKASI ADAPTASI KEBIASAAN BARU DI LINGKUNGAN KAMPUS - Sembiring, Evaliata Br; Lim, Peter (JOURNAL OF DIGITAL EDUCATION, COMMUNICATION, AND ARTS (DECA), 2020)
The Covid-2019 pandemic is one of the most dangerous virus outbreaks and has shocked the world since the end of 2019. The virus is spreading very rapidly, affecting the way people live because people are required to remain productive. Therefore, new habit adaptations are compiled and carried out as an effort to reform and support the sustainability of the economy and the activities of various sectors including education. Politeknik Negeri Batam, which plays a role in providing services to the community, is included in the category of potential crowd. Therefore, we need a guide to educate each academician about the adaptation of new habits. One of the popular technologies for people during the Covid-19 virus pandemic is Motion Graphic. The solution built in this research is a video about Adaptation to New Habits in the campus environment in the form of a 2D Motion Graphic, as one of the educational media for the campus academic community. The video development method uses Luther Sutopo method. The resulting products are analyzed for their feasibility as a medium of education and information for academics at Politeknik Negeri Batam. Video eligibility is determined based on community perceptions through respondents using the EPIC model. The results of the research are: (1) Video in the form of motion graphics using MP4 format, with a duration of 03 minutes 07 seconds, can be run on various platforms, especially accessible via online media; (2) Based on the public perception of using the EPIC dimension, the average achievement is 90.7%, so that the video is considered very effective as an educational medium to inform about the use of elevators in the campus environment during the Covid-19 pandemic.